La réponse des pays ACP au document de travail interne de la Commission - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2003)
Les exportateurs de sucre des pays ACP ont exprimé leurs...